2020
DOI: 10.1002/adma.202005423
|View full text |Cite
|
Sign up to set email alerts
|

Defect‐Rich Adhesive Molybdenum Disulfide/rGO Vertical Heterostructures with Enhanced Nanozyme Activity for Smart Bacterial Killing Application

Abstract: Nanomaterials with intrinsic enzyme-like activities, namely "nanozymes," are showing increasing potential as a new type of broad-spectrum antibiotics. However, their feasibility is still far from satisfactory, due to their low catalytic activity, poor bacterial capturing capacity, and complicated material design. Herein, a facile synthesis of a defect-rich adhesive molybdenum disulfide (MoS 2)/rGO vertical heterostructure (VHS) through a one-step microwave-assisted hydrothermal method is reported. This simple,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
144
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 240 publications
(153 citation statements)
references
References 54 publications
3
144
1
Order By: Relevance
“…to generate more active edge sites exposure for further improving the catalytic activity. 61,64 It was also reported that the thinner MoS 2 /GO composites with better conductivity had higher catalytic activity than that of thicker one. 35,65 The employment of proper synthetic strategies is the main factor in the low-cost synthesis of nanozymes with high yield and high catalytic activity, which is a significant advantage when compared with nature enzymes.…”
Section: Synthesis Of Mo-based Nanozymesmentioning
confidence: 96%
“…to generate more active edge sites exposure for further improving the catalytic activity. 61,64 It was also reported that the thinner MoS 2 /GO composites with better conductivity had higher catalytic activity than that of thicker one. 35,65 The employment of proper synthetic strategies is the main factor in the low-cost synthesis of nanozymes with high yield and high catalytic activity, which is a significant advantage when compared with nature enzymes.…”
Section: Synthesis Of Mo-based Nanozymesmentioning
confidence: 96%
“…Recently, artificial mimic enzymes have been developed to overcome the shortcomings of natural ones. [ 32–37 ] Artificial nucleases mimic the hydrolytic cleavage of phosphodiester bond by taking advantage of multinuclear metal complexes, including transition metals and rare earth elements such as Cu(II), Cr(III), Zn(II), Ce(IV). [ 38–42 ] Among them, cerium complex has attracted considerable attention due to its high catalytic efficiency and good biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…[15] Thep eroxidase (POD)-mimicking nanozyme can catalyze H 2 O 2 into highly cytotoxic hydroxyl radicals (•OH) to enhance intracellular oxidative stress. [16] Although the overexpressed GSH as ROSscavenger in cancer cells poses agreat threat for ROS-augmented cancer treatments,the glutathione oxidase (GSHOx)-mimickingn anozyme can catalyze GSH into glutathione disulfide (GSSG) to reduce the intracellular GSH content. [17] However,f or the majority of reported nanozymes,o nly as mall portion of superficial active-site atoms can devote to the enzyme-like catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, with specific response to the unique tumor microenvironment (TME) featuring mild acidity, over‐produced hydrogen peroxide (H 2 O 2 ) and glutathione (GSH), nanozymes show a bright prospect in tumor‐specific nanocatalytic therapy by regulating intracellular biochemical processes [15] . The peroxidase (POD)‐mimicking nanozyme can catalyze H 2 O 2 into highly cytotoxic hydroxyl radicals (⋅OH) to enhance intracellular oxidative stress [16] . Although the overexpressed GSH as ROS scavenger in cancer cells poses a great threat for ROS‐augmented cancer treatments, the glutathione oxidase (GSHOx)‐mimicking nanozyme can catalyze GSH into glutathione disulfide (GSSG) to reduce the intracellular GSH content [17] .…”
Section: Introductionmentioning
confidence: 99%